Automated System-Wide Protection System Performance Review and Setting Improvement - Bopp, Thomas; Krebs, Rainer; Ganjavi, Reza; Ntsin, B; Dauer, Maximilian; Jäger, Johann (pacworld, 2014)
This paper presents a new validated method for evaluating the protection system performance and determining improved sets of new settings. The protection system of a nation-wide power system has been reviewed and improved automatically by a computer-based assessment and a rule-based relay setting calculation. Key findings derived from the practical application were summarized. Protection coordination and verification of settings through separate simulations is getting increasingly complex. Conventional protection coordination and simulation tools reach their limits of practical applicability for fast developing networks and changing operating conditions. The absence of efficient tools is one reason that systematic evaluations of the protection systems performance cannot be carried out. New automated protection security assessment solutions can overcome existing limitations and allow the fast and systematic performance assessment of the protection system. This paper presents a novel approach to assess the adequacy and limitations of protection settings and schemes. It facilitates the verification of pick-up safety and selectivity of protection settings for large numbers of different fault and operation scenarios that have to be examined with respect to the different characteristics of the protection devices. The presented solution is capable to handle large and complex network structures, and also to analyze the system behavior of the protection system and network as a whole. New concise result visualizations were developed to support protection engineers and operators to identify potential weak points and limitations of the protection schemes and settings. The paper summarizes key findings and lessons learnt from an automated systematic protection performance assessment and enhancement project performed on a nationwide transmission system. It demonstrates how the applied solution can help to assure and improve the quality of protection settings through event-triggered or regular application. The in-depth evaluation allows the pinpointing of false settings in individual relays and for various different operating and fault conditions. If false or improvable settings are detected then the solution supports the calculation of new improved protection settings. To enhance quality control, a new set of settings can be validated and verified through simulation before application in order to maximize network utilization and grid reliability by reducing the risk of unwanted protection actions and cascading event
Keywords: Protection Security Assessment; Protection Performance; Relay Setting Calculation; Protection Coordination

Computer-based optimization of protection system design and coordination - Dauer, Maximilian; Jäger, Johann (IEEE Power and Energy Society General Meeting, 14PESGM2706, 2014)

Digital System Protection Design – A New Toolchain For Protection System Automation - Meyer, Janick; Biller, Martin; Jäger, Johann; Dauer, Maximilian; Romeis, Christian; Krebs, Rainer; Shang-Jaeger, Li; Schäkel, Nils; Braun, Benjamin; Stumpe, Maximilian; Tünnerhoff, Philipp (CIRED 2019, International Conference on Electricity Distribution, 2019)
This paper is proposing an integrated digital toolchain for the design and parametrization of protection relays. The process flow is fully digitized and automated. It considers the grid and the protection behavior as a whole with the use of integrated grid and protection models. Thus it can be adapted highly flexible to frequent changing grid conditions. Moreover an optimization tool finds the best feasible solution of the protection system concerning the supply reliability under diverse grid conditions. A case study illustrates the functioning of that process and the results to be achieved.Future power grids are facing an increased diversity of operation and disturbance conditions. These are caused by fluctuating infeeds of renewable energy sources as well as the use of unconventional grid devices like voltage source converters or short-circuit current limiters. Maintaining a high degree of supply reliability, the protection systems and their design process have to be adapted to the changing conditions.This paper is proposing an integrated digital toolchain for the design and parametrization of protection relays. The process flow is fully digitized and automated. It considers the grid and the protection behavior as a whole with the use of integrated grid and protection models. Thus it can be adapted highly flexible to frequent changing grid conditions. Moreover an optimization tool finds the best feasible solution of the protection system concerning the supply reliability under diverse grid conditions. A case study illustrates the functioning of that process and the results to be achieve

EPSODE Algorithm for System-Wide Protection Coordination - Meyer, Janick; Dauer, Maximilian; Krebs, Rainer; Bopp, Thomas; Jäger, Johann (19th Power Systems Computation Conference (PSCC), 2016)
This paper presents a fully automated methodology for the coordination of the protection system of a system-wide power network. The introduced metaheuristic is capable of handling different protection schemes and complex network structures.A metaheuristic consists of three basic elements: mathematical representation of the problem, a fitness function and the optimization algorithm. A new variant of the Particle Swarm Optimization (PSO) algorithm is presented to solve this challenge as well as possible. This paper makes use of previously published works and focuses on the optimization algorithm. Nevertheless the method was applied to a real transmission network. The results are discussed and rated and the effectiveness is pinpointed.
Keywords: Power System Protection; Power System Reliability; Particle Swarm Optimization; Differential Evolution; Protection Security Assessment

Erfahrungen mit einer systematischen Schutzbewertung in Verteilungsnetzen - Blug, Christian; Shang-Jaeger, Li; Bopp, Thomas; Krebs, Rainer; Dauer, Maximilian; Jäger, Johann (9. ETG-/FNN-Tutorial Schutz- und Leittechnik, 2016)

Flexible Schutzbewertung für multivariate Netze anhand fuzzifizierter Einstellparameter des Distanzschutzes - Meyer, Janick; Dauer, Maximilian; Krebs, Rainer; Jäger, Johann (ETG-CIRED-Workshop 2018 (D-A-CH), 2018)
Zwei wesentliche Änderungen in der gegenwärtigen Stromversorgung können beobachtet werden: zunehmender Leistungsaustausch im Verteilnetz und Ausbau dezentraler Erzeugungseinheiten. Das elektrische Energienetz ist hierdurch starken Änderungen ausgesetzt. Die volatilen Quellen führen zu unterschiedlichen Lastflüssen (Richtungen) und damit zu unterschiedlichen Ausgangssituationen für die Schutzsicherheit. Fehlerhafte Einstellungen der Backup-Zonen der Distanzschutzrelais führten in den letzten Jahren zu zahlreichen Blackouts. Um dies zu überwinden, sind häufige und schnelle Neuberechnungen der Schutzeinstellungen die offensichtliche Lösung. Doch traditionelle Schutzeinstellregeln nach Ziegler oder Nerc, die jedem Schutzingenieur ein Begriff sind, sind hierfür jedoch nicht ausreichend. Es bedarf neuer adaptiver Einstellregeln, die sich neuen und multivarianten Netzsituationen anpassen. Dieses Papier verwendet hierbei die Methode der Fuzzifizierung von den zwei wichtigsten Kriterien in der Schutztechnik: Selektivität und Sicherheit. Meistens sind die Einstellungen aufgrund spezieller Netzwerkvereinbarungen, verschiedener Beratungsunternehmen und anderer lokaler Merkmale nicht streng auf eine gemeinsame Methodik festgelegt. Die Verwendung einer einzigen Methode für das gesamte System könnte das Verhalten des Schutzsystems als Ganzes verbessern. Es wird ein neues Einstellkonzept vorgestellt, das über Optimierungsalgorithmen gelöst wird uns zu einer eindeutigen Lösung kommt

Improving grid reliability through application of protection security assessment - Bopp, T. A.; Ganjavi, R.; Krebs, R.; Ntsin, B.; Dauer, Maximilian; Jäger, Johann (IET Conference Publications, 2014)
Key findings derived by the application of an automated protection security assessment solution on a nationwide transmission system are presented. Protection coordination and verification of settings through simulation is getting increasingly complex. Conventional protection coordination and simulation tools reach their limits of practical applicability for fast developing networks and changing operating conditions. New automated protection security assessment solutions can overcome existing limitations and allow the fast and systematic performance assessment of the protection system. A new approach to assess the adequacy of protection settings and schemes is presented. It facilitates the verification of selectivity of protection settings for large numbers of different operation and fault scenarios. The presented solution is capable to handle large and complex network structures, and also to analyze the system behavior of the protection system and network as a whole. New concise result visualizations were developed to support protection engineers and operators to identify potential weak points and limitations of the protection schemes and settings. The paper summarizes key findings and lessons learnt from an automated systematic protection performance assessment and enhancement project performed on a nationwide transmission system. It demonstrates how the applied solution can help to assure and improve the quality of protection settings through event-triggered or regular application. The in-depth evaluation allows the pinpointing of false settings in individual relays and for various different operating and fault conditions. If false or improvable settings are detected then the solution supports the calculation of new improved protection settings. To enhance quality control, a new set of settings can be validated and verified through simulation before application in order to maximize network utilization and grid reliability by reducing the risk of unwanted protection actions and cascading events.
Created from Fastlane, Scopus look-up
Keywords: Automated protection performance assessment

Protection Security Assessment - Eine wichtige Aufgabe in Netzen mit dezentraler Energieversorgung - Bopp, Thomas; Krebs, Rainer; Jäger, Johann; Dauer, Maximilian (7. ETG/FNN Tutorial "Schutz- und Leittechnik", 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.protec

Protection Security Assessment - Fuzzification of Relay Settings for Weak Spot Detection - Dauer, Maximilian; Jäger, Johann; Bopp, Thomas; Krebs, Rainer (APAP Protection and Automation Conference, 2013)
This paper addresses the challenge of weak spot detection of a proposed protection scheme. The presented method analyzes the protection system of a power network and checks for limits of the setting methodology. The approach is useful for system-wide analysis. A fuzzy system was developed therefore. Fuzzificated values are computer-readable linguistic values. They can describe the system in a more detailed way, as an engineer would do. The use of a fuzzy system enables the possibility of integration in an automated application. This method is system-wide, knowledge-based and self-adaptive. To validate this benefit a comparison has been done between the fuzzy system and the commonly proofed method fingerprint analysis. The paper demonstrates the capability of the presented fuzzy system to detect weak spots of the protection system globally, to find the reason for this in a suboptimal methodology and to calculate these findings very fast. Index Terms-fingerprint analysis, fuzzy logic, power system reliability and security, power system planning, power system protection, protection security assessme

Protection Security Assessment - Innovative Strategies and Methods for Future Networks - Jäger, Johann; Fuchs, Jochen; Dauer, Maximilian; Bopp, Thomas; Krebs, Rainer (Power and Energy Society General Meeting, 2012)
This paper presents new strategies and methods for assessing the security of protection systems and for protection system adaption to reduce the risk of unnecessary disturbances and blackouts. The introduced algorithms are capable to handle complex network structures. Hence, the system behavior of a protection system and network is analyzed and assessed as a whole. Protection security assessment can be investigated under two different aspects: on the one hand the behavior regarding selectivity, speed and sensitivity and on the other hand the behavior regarding the response on dynamic network phenomena as voltage stability and transient stability. A new automated method, called SIGUARD ® PSA for assessing the security, selectivity and speed of protection systems is shown. The simulation tool PSS®SINCAL is used to provide a holistic simulation system of network and protection devices. The handling of the large amount of resulting data is done by an intelligent visualization method like a fingerprint analysis. Further on the paper is focused on the protection response on dynamic network phenomena and presents innovative strategies for this investigation aspect. Applicable protection models and the simulation environment based on PSS®NETOMAC will be described. Finally new strategies of protection adaption will be shown based on case studies of real networks. © 2012 IEEE.
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.protec_1
Keywords: Protection security assessment; adaptive settings; dynamic protection simulation; generic protection models; protection coordination; selectivity; speed

Protection security assessment - System evaluation based on fuzzification of protection settings - Dauer, Maximilian; Jäger, Johann; Bopp, Thomas; Krebs, Rainer (2013 4th IEEE/PES Innovative Smart Grid Technologies Europe, ISGT Europe 2013, 2013)
This paper presents a new method for an automated weak spot detection of the protection system of electrical energy systems. The intent was to find a fast and holistic approach. To fulfill the holistic requirement the settings of all relays should be analyzed in detail. A fuzzy system was developed therefore. The use of a fuzzy system enables the possibility of integration in an automated application. To prove the benefit a comparison has been done between the fuzzy system and the commonly proofed method finger-print analysis. This paper demonstrates the capability of the presented fuzzy system to detect weak spots globally, to identify the reasons in detail and to calculate the result very fast. © 2013 IEEE.
Created from Fastlane, Scopus look-up
Keywords: evaluation; finger-print analysis; fuzzification; optimization; protection security assessment

System Operation in Novel Power Grids – A Central Topic inGermans Biggest Research Initiative for “Energiewende” - Dauer, Maximilian; Jäger, Johann (International ETG Congress 2017, 2017)